2005
DOI: 10.1016/j.pain.2004.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine and postoperative pain – a quantitative systematic review of randomised trials

Abstract: Ketamine, an N-methyl-D-aspartate receptor antagonist, is known to be analgesic and to induce psychomimetic effects. Benefits and risks of ketamine for the control of postoperative pain are not well understood. We systematically searched for randomised comparisons of ketamine with inactive controls in surgical patients, reporting on pain outcomes, opioid sparing, and adverse effects. Data were combined using a fixed effect model. Fifty-three trials (2839 patients) from 25 countries reported on a large variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
279
4
31

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 508 publications
(322 citation statements)
references
References 62 publications
8
279
4
31
Order By: Relevance
“…However, each drug and the combination produced a statistically significant and clinically important morphine-sparing effect. In fact, we observed a 37% reduction in total 48-h morphine use (26 mg) in the ketamine-only group, which is similar to the morphine-sparing effect reported previously [5]. Benefit in patients given pregabalin alone was similar.…”
Section: Discussionsupporting
confidence: 89%
“…However, each drug and the combination produced a statistically significant and clinically important morphine-sparing effect. In fact, we observed a 37% reduction in total 48-h morphine use (26 mg) in the ketamine-only group, which is similar to the morphine-sparing effect reported previously [5]. Benefit in patients given pregabalin alone was similar.…”
Section: Discussionsupporting
confidence: 89%
“…This meta-analysis has some advantages compared with the previous review 27 . The first one is that the included studies were updated up to 2012.…”
Section: Discussionmentioning
confidence: 99%
“…While the use of ketamine to reduce CPSP is empirically promising, the results still remain controversial due to the wide variability in clinical settings, ketamine regimens, and reported outcomes. In addition, some of the positive results have been obtained using clinical anesthesia regimens which are not accepted as standard treatments [55,56]. Since Chaparro et al's systematic review no ketamine trials were identified which examined CPSP outcomes.…”
Section: Ketaminementioning
confidence: 99%